The effect of cultural and social capital on early career success and satisfaction, the case of recent graduates from business schools in Portugal - Pereira, Rita Maria de Andrade (2018)
The present study summarizes a qualitative and quantitative research that was designed to understand the effect of social capital on early career success and career satisfaction, more specifically career success of recent graduates from business schools in Portugal. It aims to understand what is the effect of social reproduction on graduates’ placement, for the same level of education. The university role, as well as the role of career services in Higher Education were also considered to conduct this study, since these have been evolving in the last century due to considerable socioeconomic and technological changes, to help graduates with placement.